Ozonated Sunflower Oil Exerted Potent Anti-Inflammatory Activities with Enhanced Wound Healing and Tissue Regeneration Abilities against Acute Toxicity of Carboxymethyllysine in Zebrafish with Improved Blood Lipid Profile - Kyung-Hyun Cho; Ji-Eun Kim; Ashutosh Bahuguna; Dae-Jin Kang (MDPI AG, 2023)
Ozonated sunflower oil (OSO) is an established therapeutic agent and nutraceutical harboring various therapeutic values, including antiallergic, derma-protective, and broad-spectrum antimicrobial activity. Conversely, the medicinal aspects of OSO for wound healing, tissue regeneration, and treatment of inflammation in dyslipidemia have yet to be fully elucidated. Herein, a comparative effect of OSO and sunflower oil (SO) was investigated to heal cutaneous wound and tissue regeneration of zebrafish impediment by carboxymethyllysine (CML) toxicity, following impact on hepatic inflammation and blood lipid profile. After OSO (final 2%, 1 μL) and SO's (final 2%, 1 μL) treatment, substantial healing was elicited by OSO in the cutaneous wound of zebrafish impaired by CML (final 25 μg). As an important event of wound healing, OSO scavenges the reactive oxygen species (ROS), rescues the wound from oxidative injury, and triggers the essential molecular events for the wound closer. Furthermore, the intraperitoneal injection of OSO was noted to counter the CML-induced adversity and prompt tissue regeneration in the amputated tail fin of zebrafish. Additionally, OSO counters the CML-induced neurotoxicity and rescues the zebrafish from acute mortality and paralysis, along with meticulous recovery of hepatic inflammation, fatty liver changes, and diminished ROS and proinflammatory interleukin (IL)-6 production. Moreover, OSO efficiently ameliorated CML-induced dyslipidemia by alleviating the total blood cholesterol (TC), triglyceride (TG), and increasing high-density lipoproteins cholesterol (HDL-C). The outcome of multivariate assessment employing principal component analysis and hierarchical cluster analysis supports a superior therapeutic potential of OSO over SO against the clinical manifestation of CML. Conclusively, OSO owing to its antioxidant and anti-inflammatory potential, counters CML-induced toxicity and promotes wound healing, tissue regeneration, hepatoprotection, improved blood lipid profile, and survivability of zebrafish.